2010
DOI: 10.1111/j.1745-4603.2010.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Double (W/O/W) Emulsions Prepared With Soybean Milk and Fortified With Calcium

Abstract: The objective of this work was to study the rheological behavior of water‐in‐oil‐in‐water (w/o/w) emulsions prepared with soybean milk and sunflower oil, with different calcium solutions as the internal aqueous phase, in order to evaluate them as a vegetable substitute of whipped dairy cream. The obtained systems exhibited a creamy texture, which was attributed to the swelling of w/o droplets because of the osmotic gradient generated by the inclusion of soluble salts in the internal aqueous phase. A secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…HSPS and HSPS/SSPS have a more important effect on the magnitude of the viscoelastic parameters, probable due to the higher flocculation degree which was previously evidenced by the %FD values. Flocculation increases the viscosity of an emulsion because the effective volume fraction of a floc is greater than the sum of the volume fractions of the individual droplets due to the presence of the continuous phase trapped within it (Marquez and Wagner 2010).…”
Section: Fine O/w Emulsionsmentioning
confidence: 99%
“…HSPS and HSPS/SSPS have a more important effect on the magnitude of the viscoelastic parameters, probable due to the higher flocculation degree which was previously evidenced by the %FD values. Flocculation increases the viscosity of an emulsion because the effective volume fraction of a floc is greater than the sum of the volume fractions of the individual droplets due to the presence of the continuous phase trapped within it (Marquez and Wagner 2010).…”
Section: Fine O/w Emulsionsmentioning
confidence: 99%
“…Fat reduction has been assayed in cheese-like products formulated with W 1 /O/W 2 emulsion, closely emulating some of the textural characteristics and achieving similar preferences scores to their full milk-fat counterparts (LobatoCalleros et al, 2008). Márquez and Wagner (2010) reported that a double emulsion can work as a reduced-fat substitute for whipped dairy cream.…”
Section: Introductionmentioning
confidence: 98%
“…Hence, multiple emulsions can be used in the design and preparation of functional foods, to deal with aspects relating to improvement of lipid contents and profiles, including encapsulation to enhance the presence of bioactive (essentially hydrophilic) compounds. In this context, multiple emulsions have been used to micro-encapsulate numerous substances, including: (a) minerals (Bonnet et al, 2009;Choi, Decker, & McClements, 2009;Márquez & Wagner, 2010), (b) vitamins (Benichou, Aserin, & Garti, 2007;Li et al, 2012;O'Reagan and Mulvihill, 2009), (c) amino acids (Owusu, Zhu, & Dickinson, 1992), (d) carotenoids (Rodríguez-Huezo, Pedroza-Islas, Prado-Barragán, Beristain, & Vernon-Carter, 2004), (e) probiotics (Pimentel-González, Campos-Montiel., Lobato-Calleros, & Pedroza-Islas, 2009;Shima, Morita, Yamashita, & Adachi, 2006) and (f) resveratrol (Hemar, Cheng, Oliver, Sanguansri, & Agustin, 2010). Most of these studies have focused on the actual encapsulation process, devoting most attention to aspects relating to the formation and characterisation of W 1 /O/W 2 emulsions, which are assessed through analysis of their structure and properties, with reference to different variables associated with their composition and preparation procedure (Dickinson, 2011;McClements et al, 2009;Muschiolik, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There have been patented studies on the use of W/O/W emulsions in salty creams (salt-encapsulated) and aromatic mayonnaises (flavour-encapsulated) (de Cindio et al, 1991;Garti, 1997). Márquez and Wagner (2010) reported that a double emulsion can work as a reduced-fat substitute for whipped dairy cream. Lobato-Calleros et al (2006, 2008 carried out studies about low-fat (decreased oil content up to 26%) white cheese production by using W/O/W emulsions including canola oil stabilized with some hydrocolloids without causing considerable difference in sensorial, textural and rheological properties as compared with control groups.…”
Section: Multiple Emulsions (Multiplex/double/multilayered Emulsions)mentioning
confidence: 99%